Bacteriostatic effect of piper betle and psidium guajava extracts on dental plaque bacteria - Razak, Fathilah Abdul; Rahim, Z.H.A.; Othman, Y.; Yusoff, M. (2009)
In this study, the bacteriostatic effect of Piper betle and Psidium guajava extracts on selected early dental plaque bacteria was investigated based on changes in the doubling time (g) and specific growth rates (Î¼). Streptococcus sanguinis, Streptococcus mitis and Actinomyces sp. were cultured in Brain Heart Infusion (BHI) in the presence and absence of the extracts. The growth of bacteria was monitored periodically every 15 min over a period of 9 h to allow for a complete growth cycle. Growth profiles of the bacteria in the presence of the extracts were compared to those in the absence and deviation in the g and Î¼ were determined and analyzed. It was found that the g and Î¼ were affected by both extracts. At 4 mg mL-1 of P. betle the g-values for 5. sanguinis and 5. mitis were increased by 12.0- and 10.4-fold, respectively (p<0.05). At similar concentration P. guajava increased the g-value by 1.8- and 2.6-fold, respectively (p<0.05). The effect on Actinomyces sp. was observed at a much lower magnitude. It appears that P, betle and P, guajava extracts have bacteriostatic effect on the plaque bacteria by creating a stressed environment that had suppressed the growth and propagation of the cells. Within the context of the dental plaque, this would ensure the attainment of thin and healthy plaque. Thus, decoctions of these plants would be suitable if used in the control of dental plaque. Â© 2009 Asian Network for Scientific Information.